Gentamicin-induced structural damage of human and artificial (biomimetic) otoconia. (February 2014) - Walther, Leif Erik; Wenzel, Angela; Buder, Jana; Blödow, Alexander; Kniep, Rüdiger
Abstract Conclusions: Gentamicin causes irreversible structural damage of human and artificial otoconia by progressive dissolution of calcite. The inner architecture of otoconia is strongly affected by degradation scenarios during gentamicin exposure. Artificial otoconia can be used as a model system mimicking the chemical attacks for detailed investigations. Objectives: To investigate the chemical interactions of gentamicin with natural calcite and human and artificial otoconia under in vivo conditions. Methods: Pure calcite crystals and artificial and human otoconia were exposed to gentamicin injection solutions at various concentrations. Morphological changes were observed in time steps by the use of environmental scanning electron microscopy (ESEM). Results: Dissolution of pure calcite crystals results in the formation of well oriented nanoshoots indicating an irreversible chemical reaction with gentamicin. Human and artificial otoconia reveal irreversible structural changes of their surface areas as well as of their inner structure, resulting in characteristic changes at different gentamicin concentrations. Minor changes are first observed by surface alterations and dissolution of calcite in the belly region. Major changes result in further reduction of the belly area reaching the center of symmetry. Finally, a complete dissolution of the branches takes place. Artificial otoconia provide detailed insight into surface alterations.